Efficient purification of wastewater by applying mechanical force and BaCO3/TiO2 and BaTiO3/TiO2 piezocatalysts. Issue 59 (18th November 2021) - Amiri, Omid; Ahmed, Haval Aziz; Abdan, Abdulla Ahmed; Mahmood, Peshawa H.; Salavati-Niasari, Masoud
Abstract : In typical advanced oxidation catalysis, a semiconductor should have a robust capacity to generate separated electron–hole pairs on a material's surface under irradiation of photons with energy more than the material's bandgap. Abstract : In typical advanced oxidation catalysis, a semiconductor should have a robust capacity to generate separated electron–hole pairs on a material's surface under irradiation of photons with energy more than the material's bandgap. However, rapid charge carrier recombination and low photon to current yield of semiconductor photocatalysts and low percentages of UV light in sunlight leads to a low level of photocatalytic efficiency for practical application. Mechanical energy is a natural energy that can be considered as a form of rich, clean and renewable energy which can be harvested by using piezoelectric materials. Here, we developed BaCO3 /TiO2 and BaTiO3 /TiO2 composites as mechanical harvesting materials to decontaminate pollutants. Results showed that BaCO3 has a great effect on the piezocatalytic activity of products. The control sample (sample without Ba) only degraded 11.2% of Acid Red 151 (AR151), while the sample containing Ba degraded 96.7% of AR151. Besides, the effects of several parameters, including the natural surfactant, reaction time and temperature, calcination, and ultrasonic power and pulse on the catalytic activity of the as-prepared piezocatalysts were studied. Results showed that it is possible to degrade 99.1% of AR151 by controlling ultrasonic parameters during 2 h of mechanical energy force.